Time series analysis of river water quality data from a tropical urban catchment - Chow M.F.; Haris H.; Sidek L.M. (CRC Press/Balkema, 2023)
Ammonia; Catchments; Chemical analysis; Parameter estimation; Rivers; Runoff; Time series analysis; Tropics; Wastewater treatment; Water quality; Average concentration; Long term change; Mann-Kendall test; Physical and chemical parameters; River water quality; Water quality indexes; Water quality parameters; Water quality standard; Quality control